Management of patients with systemic lupus erythematosus in real clinical practice - E. A. Aseeva; S. K. Soloviev; T. V. Popkova; N. Yu. Nikishina; A. A. Mesnyankina (Научно-практическая ревматология, 2019)
Recommendations for the management of patients with systemic lupus erythematosus (SLE) in real clinical practice are presented. They take into account the course, activity, damage, and consider assessment of these parameters with validated indices. The characteristic of therapeutic schemes is given, features of monitoring of patients with SLE are considered.